(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background: Treatment of drug-resistant tuberculosis is often based on drug susceptibility testing results. Thus simple, rapid and economic test is very important for diagnosis of drug resistant tuberculosis and such method aids in TB control effectively. One such method is a Nitrate Reductase Assay (NRA). Objective: To evaluate feasibility and performance of Nitrate Reductase Assay in the screening of drug-resistant tuberculosis. Setting: National Tuberculosis Centre and SAARC TB and HIV/AIDS Centre, Thimi, Bhaktapur, Nepal from April 2008 to March 2009. Methods: A prospective study comparing the sensitivity and specificity of the Nitrate Reductase Assay with the gold standard Lowenstein Jensen proportion method in determining drug susceptibility pattern to four primary anti-tubercular drugs i.e. isoniazid, rifampicin, streptomycin and ethambutal among clinical isolates. Results: Among 121 specimens , the sensitivity and specificity of the Nitrate Reductase Assay for detection of Isoniazid resistance was 100% and 91%, for rifampicin was 100% and 98.95%, for streptomycin was 96% and 91.66% and for ethambutal was 100% and 98% respectively. Conclusions: The Nitrate Reductase Assay is sensitive and specific enough for the detection of drug resistant tuberculosis. It is rapid, easy to use and inexpensive, making it suitable for developing countries. Its usefulness for national drug resistance surveys should be assessed. Keywords: diagnosis; drug resistance; sensitivity; specificity; NRA DOI: 10.3126/saarctb.v7i1.3960 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(1) 26-30